Regular dusting of dried fish - Mumbai Archive Project Team (Jio Institute, 2024)
The sun-drying process may take several days or weeks, depending on factors such as temperature, humidity, and fish size. Regular dusting ensures the dried fish are evenly exposed to sunlight.